Modeling the Heterodimer Interfaces of Melatonin Receptors - Tse, Lap Hang; Wong, Yung Hou (Frontiers in Cellular Neuroscience, 2021)
Melatonin receptors are Class A G protein-coupled receptors (GPCRs) that regulate a plethora of physiological activities in response to the rhythmic secretion of melatonin from the pineal gland. Melatonin is a key regulator in the control of circadian rhythm and has multiple functional roles in retinal physiology, memory, immunomodulation and tumorigenesis. The two subtypes of human melatonin receptors, termed MT1 and MT2, utilize overlapping signaling pathways although biased signaling properties have been reported in some cellular systems. With the emerging concept of GPCR dimerization, melatonin receptor heterodimers have been proposed to participate in system-biased signaling. Here, we used computational approaches to map the dimerization interfaces of known heterodimers of melatonin receptors, including MT1/MT2, MT1/GPR50, MT2/GPR50, and MT2/5-HT2C. By homology modeling and membrane protein docking analyses, we have identified putative preferred interface interactions within the different pairs of melatonin receptor dimers and provided plausible structural explanations for some of the unique pharmacological features of specific heterodimers previously reported. A thorough understanding of the molecular basis of melatonin receptor heterodimers may enable the development of new therapeutic approaches against aliments involving these heterodimeric receptors.